Public Private Partnerships for Resilient Communities - Pelizzaro, Piero (TeMA - Journal of Land Use, Mobility and Environment, 2015)
This article focuses on the role of local institutions in mitigation and adaptation to climate change, considering learning experiences in promoting public-private partnerships in to resilient actions. It does so under the belief that climate impacts will affect disadvantaged social groups and small-communities more disproportionately, and that local institutions centrally influence how different social groups gain access to and are able to use assets and resources. Looking at the increasing awareness that global temperatures will raise, a mentality "Climate-smart" must be adopted by all levels of decision-making. This approach involves the search for synergies between climate change mitigation and adaptation, wherever is possible. As for mitigation, for adaptation we consider similar pre-conditions. Base on this pre-conditions we identify Public Private Partnerships as a challenge possibility to finance decentralized renewable energies and green infrastructure for resilient communities. The article aims to demonstrate two main unclear topics in existing understanding about institutions and climate change responses: the correlation among Public Private Partnerships and participatory process and how it lead to win-win climate responses funding, a learning experience from Sustainable Energy Action Plan - Within the MED Programme project ZeroCO2[1] - and Local Adaptation Plan development – within the LIFE+ project BLUE AP[2]. [1] Kyoto Club was partner of the MED Project ZERO CO2 www.medzeroco2.eu [2] Kyoto Club is partner of the LIFE+ Project BLUE AP Bologna Local Urban Environment Adaptation Plan for Resilient City – www.blueap.eu